Diagnostic accuracy and reliability of the neurological and arterial tests according to the IWGDF guidelines in the diagnosis of diabetic peripheral neuropathy and peripheral arterial disease in type 2 diabetic patients attending the primary health care - Rodríguez Alonso, Dante (2018)
Objective: To determine the diagnostic accuracy and reliability of the neurological test (NT) and the arterial test (AT) according to the International Working Group on the Diabetic Foot (IWGDF) guidelines in the diagnosis of diabetic peripheral neuropathy (DPN) and peripheral arterial disease (PAD), respectively, using variables such as sensitivity (Se), specificity (Sp), positive predictive value (PPV), and positive likelihood ratio (PLR) in type 2 diabetic patients attending the primary health care. Materials and methods: One hundred (100) type 2 diabetic patients were chosen from the public primary health care system, and evaluated by a primary physician in a private diabetic foot unit. The NT was represented by the tactile-vibratory sensitivity and the AT by the ankle-brachial index according to the IWGDF guidelines. They were compared to standard neurological and arterial tests called Michigan Neuropathy Screening Instrument and Duplex Doppler Ultrasound, respectively, and performed by a diabetic foot specialist. Results: The NT showed an Se and Sp of 100 % and 94 % for the DPN, and the AT showed an S and E of 67.3 % and 83.2 % for the PAD, as well as a high PPV. The PLR was good in the NT, but poor in the AT. Conclusions: Accuracy and reliability of the NT and AT according to the IWGDF guidelines were adequate to diagnose DPN and PAD, respectively, in type 2 diabetic patients attending the primary health care, whose values were very similar to other studies’ but affected by local factors.